Corpos Marcados: uma reflexão Sobre o corpo feminino no Cristianismo Primitivo a partir de atos de Pedro - Ramos, Wiviane Marina Pires (2021)
The purpose of this research is to reflect on the female body from the book Acts of Peter. The proposed theme discusses a subject that still causes discomfort in the churches of today, that is, the female body. Women and their bodies have always been the target of criticism, seen as object to be controlled by patriarchal society. Faced with an androcentric structure, their bodies have directly suffered all kinds of violence. When examining the Acts of Peter, one of the accounts contained in this book tells the story of the daughter of the apostle who remains paralyzed after being targeted by a man. This research sought to expose the thought that primitive Christianity about the female body from this account of the daughter of the apostle. This account was studied through the narrative analysis bias. We first presented the view of sexuality in Greco-Roman society about the role of women and their bodies. We seek to make an analysis of the narrative of the text of the apostle's daughter to understand issues that involved the paralysis of this woman and how sexual renunciation allowed freedom for the bodies of women